Cryptocurrency investing for dummies eaudiobook - Danial, Kiana (Tantor Media, 2020)
While the cryptocurrency market is known for its volatility—and this volatility is often linked to the ever-changing regulatory environment of the industry—the entire cryptocurrency market is expected to reach a total value of $1 trillion this year. If you want to get in on the action, this book shows you how. Cryptocurrency Investing For Dummies offers trusted guidance on how to make money trading and investing in the top 200 digital currencies, no matter what the market sentiment. You'll find out how to navigate the new digital finance landscape and choose the right cryptocurrency for different situations with the help of real-world examples that show you how to maximize your cryptocurrency wallet. ● Understand how the cryptocurrency market works ● Find best practices for choosing the right cryptocurrency ● Explore new financial opportunities ● Choose the right platforms to make the best investments This book explores the hot topics and market moving events affecting cryptocurrency prices and shows you how to develop the smartest investment strategies based on your unique risk tolerance.